2015
DOI: 10.1039/c4tb01724b
|View full text |Cite|
|
Sign up to set email alerts
|

Reversible PEGylation and Schiff-base linked imidazole modification of polylysine for high-performance gene delivery

Abstract: Gene carriers made from polylysine are of interest in relation to gene therapy but suffer from the lack of transfection efficiency due to limited stability and endosomal escape ability. To address this problem, we designed and developed Schiff-base linked imidazole modified polylysine with a reversible-PEGylation catiomer (SL-ImPEG-SS-PLL) for high efficiency gene delivery. The reversible PEGylation was introduced for in vivo circulation, as well as selective PEG detachment to augment the cellular internalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 64 publications
(103 reference statements)
1
22
0
Order By: Relevance
“…Therefore, numerous efforts have been directed towards producing non-viral gene carriers (artificial viruses) for the safe delivery of DNA and RNA interference (RNAi). [25][26][27][28][29][30] For instance, Kumar et al prepared new lipopolymers in which low molecular weight and branched polyethylene amine (LMW PEI) molecules hydrophobically modified with ferrocene-terminated alkyl tails. Their results showed a greater transfection efficiency as compared to high molecular weight PEI (25 kDa) and commercially available transfection agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, numerous efforts have been directed towards producing non-viral gene carriers (artificial viruses) for the safe delivery of DNA and RNA interference (RNAi). [25][26][27][28][29][30] For instance, Kumar et al prepared new lipopolymers in which low molecular weight and branched polyethylene amine (LMW PEI) molecules hydrophobically modified with ferrocene-terminated alkyl tails. Their results showed a greater transfection efficiency as compared to high molecular weight PEI (25 kDa) and commercially available transfection agents.…”
Section: Introductionmentioning
confidence: 99%
“…27 In another study, a new multifunctional gene carrier was prepared via crosslinking LMW PEI with lactitol diacrylate (LDA) which caused higher cellular uptake, cell targeting, and a rapid intracellular release of genes in vitro and in vivo. 28 To date, chitosan (CS), a natural linear cationic polysaccharide with a random distribution of N-acetylglucosamine (GlcNAc) and glucosamine (GlcN) units, has gained much attention as a gene delivery vector owing to its biocompatibility, low immunogenicity, ease of modification, and biodegradability. 31,32 Although CS primary amino groups can be readily protonated at low pH, its poor solubility under physiological conditions (pH B 7.0) and rather low transfection efficiency in vitro and in vivo have significantly confined its extensive applications in the biomedical domain.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 The PEG grafted or copolymerized polymer complex with anionic DNA produced core-shell polymeric micelles, where the polycation-DNA complex made up the core and the hydrophilic PEG segment made up the shell. 26,27 As a moiety of histamine, an imidazole ring has been employed to modify polymeric vectors for enhancing biocompatibility and gene transfection efficiency due to its buffering capacity near endosomal pH, which promotes a fast endosomal escape via the so-called ''proton sponge'' effect. 19,21,22 For instance, compared to PLL/DNA complexes, polyion complex micelles from complexes of PEG-b-PLL with DNA have exhibited high stability in a serum containing medium and prolonged blood circulation in experimental animals.…”
Section: Introductionmentioning
confidence: 99%
“…It has been confirmed that the hydrophilic PEG-shell can increase colloidal solubility, reduce systematic toxicity and improve circulation time. [26][27][28][29] Moreover, considering the deprotonation as the physiological pH, the imidazole moiety was further quaternized for the improvement of DNA-binding ability. 23 Moreover, Kataoka's group firstly compared the different dynamic states of polyplexes and PEGylated polyplex micelles in the bloodstream, and demonstrated the significance of PEGylation to prevent polyplex agglomeration in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PLL has high positive charge density which will cause undesirable cytotoxicity. So, when used as biomaterial, biocompatibility, toxicity, and buffering capacity of PLL should be improved, conjugating with various hydrophilic or amphiphilic polymers can realize desirable modifications …”
Section: Introductionmentioning
confidence: 99%